Folk dolls as a universal object in psychotherapeutic work with women - Bochkarjova Іolanta; Zaichikova Т. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2017)
The article is devoted to the analysis of the potential of Slavic rag doll in modern psychotherapeutic practice (Doll-therapy, the method of Art- therapy). It examines the phenomenon of ethnic dolls as psychotherapeutic object, as well as shows the versatility of slavic dolls in therapeutic practice of psychodynamic approach, Jung’s analysis, transactional analysis and Gestalt-therapy. A folk doll represents a unique tool in psychotherapeutic work with women.